Implications of migration on employment and occupational transitions in Tanzania - Mueller, Valerie; Schmidt, Emily; Lozano, Nancy; Murray, Siobhan (SAGE Publications, 2019)
The overarching message from the growth literature is that a transition from the low-productivity agricultural sector to the high-productivity manufacturing sector is necessary for structural change. Although sub-Saharan Africa has experienced substantial economic growth rates, rural–urban migration contributed very little to this progress. Migration to peri-urban areas may offer prospects for diversification out of agriculture with lower moving costs and job-search frictions than urban centers. We document migration patterns and worker selection into peri-urban and urban areas in Tanzania. Standard spatial classifications mask the prominent phenomenon of peri-urban (rather than rural) to urban migration. Lacking job experience and social networks, many youth moving to urban destinations are more likely to be unemployed. However, conditional on being employed over the two-year period of the study, migration to peri-urban as well as urban areas allows workers to transition from low- to high-valued occupations.